(untitled) (Baghdad Science Journal, 2011)
In this work the corrosion behavior of Al metal was studied by using non- destructive testing (NDT), which is a noninvasive technique for determining the integrity of a material. The ultrasonic waves was used to measure the corrosion which occur by two corrosive medium (0.1N sodium chloride and 0.1N sodium hydroxide) and study the corrosion by weight-loss method and electrochemical method in addition to performance the microscopic inspection for the samples before and after the immersion in the corrosive medium. Corrosion parameters were interpreted in these media which involve corrosion potential (Ecorr) and corrosion current density (icorr). The results indicate that both media was corrosive but the 0.1N NaOH was more corrosive than 0.1N NaCI. Micro hardness test indicates that, the hardness value of the testing metal is decrease in 0.1N NaOH solution more than 0.1N NaCl solution with longest time of immersion.